Effects of Human Electro‐Muscular Incapacitation (HEMI) Devices on Cardiovascular Changes in Anesthetized Swine as Measured by Transesophageal Echocardiography (TEE)1. Issue 2 (14th May 2018) - Werner, Jacob R.; Murray, W. Bosseau; Kennett, Mary J.; Jenkins, David M.; Liszka, Edward; Hughes, Edward L.
Abstract: The abundance of, and reliance upon, human electro‐muscular incapacitation (HEMI) devices, especially in law enforcement, has generated scrutiny and examination of these technologies. The purpose of this study was to examine cardiovascular effects resulting from typical (5 sec) and longer activation (20 sec) HEMI applications studying myocardial function and peripheral vascular system using a combination of invasive cardiovascular catheters and transesophageal echocardiography (TEE). Six healthy swine ( Sus scrofa ) 3–5 months in age and weighing between 60 and 86 kg were anesthetized and exposed to the TASER Model X26 waveform while transesophageal echocardiography was performed. Stroke volume was shown to statistically decrease during HEMI application indicating an increase in systemic vascular resistance, but HEMI application did not result in myocardial dysfunction ("cardiac stunning").